All‐Dielectric Crescent Metasurface Sensor Driven by Bound States in the Continuum. (15th August 2021) - Wang, Juan; Kühne, Julius; Karamanos, Theodosios; Rockstuhl, Carsten; Maier, Stefan A.; Tittl, Andreas
Abstract: Metasurfaces based on quasi‐bound states in the continuum (quasi‐BICs) constitute an emerging toolkit in nanophotonic sensing as they sustain high quality factor resonances and substantial near‐field enhancements. It is demonstrated that silicon metasurfaces composed of crescent shaped meta‐atoms provide tailored light‐matter interaction controlled by the crescent geometry. Significantly, this metasurface not only exhibits a fundamental quasi‐BIC resonance, but also supports a higher‐order resonance with tunable electromagnetic field enhancement and advantageous properties for sensing. The higher‐order resonance shows twice the sensitivity of the fundamental one for bulk refractive index sensing. It is further demonstrated that both the fundamental and higher‐order resonances can be exploited for sensing ultrathin layers of biomolecules in air and buffer solutions. Specifically, when measuring in buffer solution, the figure of merit of the sensor, defined as the change in the spectral position of the resonance normalized to its full width at half maximum, is a factor of 2.5 larger for the higher‐order resonance when compared to the fundamental one. Due to its high sensitivity and potential for straightforward microfluidic integration, the silicon crescent metasurface is ideally suited for real‐time and in situ biosensing, enabling compact sensing devices for a wide range of diagnostic applications. Abstract : An all‐dielectric crescent silicon metasurface serving as an efficient optical sensor is achieved. This sensing platform is driven by quasi‐bound states in the continuum with well‐tailored high quality factors of excited resonances and enhanced near‐fields, thus enabling refractive index sensing and ultrathin biomolecular detection both in air and buffer with high sensitivity and a low detection limit.